Correlation between erosion and energy consumption of sandstones - Patanapongsonti, Sarusa; Sitthimongkol, Laksikar; Thongprapha, Thanittha; Fuenkajorn, Kittitep (Engineering and Applied Science Research, 2024)
This study aims at simulating rock erosion by slake durability testing under wet and dry conditions. Phra Wihan sandstone and conglomeratic and bedded sandstones from Phu Phan formation are used as rock specimens. The test parameters are modified from the standard to accelerate the erosion process, where 2,000 drum revolutions are used instead of 200 revolutions for up to 80 test cycles (80 days). Results indicate that fragment roundness and sphericity increase with test cycles. Bedding planes reduce the roundness of bedded sandstone as the fragments become smaller. Phra Wihan sandstone is physically insensitive to water. The water-sensitive and soft Phu Phan sandstone, however, shows notable increases of porosity and reduction of density under both wet and dry conditions. Scrubbing and colliding processes mainly reduce the fragment sizes, under dry condition. Under submerging condition, even though fragment weight is decreased by its buoyancy force, intergranular bonding of the two Phu Phan sandstones is weakened by water penetration, leading to higher percentage of passing materials and lower energy required to disintegrate the rocks than under dry condition. Water insensitive Phra Wihan sandstone erodes more quickly under dry condition than under wet condition. Even though it requires longer period to erode under water submersion, due to buoyancy force, it consumes less energy than those under dry condition to reach the same fragment sizes. Larger sandstone fragments use energy more efficiently to reduce their size than the smaller ones.